The Relationships Between Single Nucleotide Polymorphisme (rs867500) STX1A Gene Exon 10 and Intelectual Intelligence - Dalinur Qur'andini; Yuwono Yuwono; Triwani Triwani (HM Publisher, 2017)
Background: STX1A consists of 10 exons covering a genome overlay of 20.42 kb (2064 base mRNA) . The location of HPC-1 / Syntaxin 1A is on chromosome 7q11.23. Genes STX1A or HPC-1 or Syntaxin 1A are genes that encode membrane proteins that play an important role in neurotransmitter exocytosis in nerve cells. Aim of Study: The purpose of this study was to determine the relationship SNP (rs867500) in the gene STX1A Exon 10 with level intellect. Method: This research was observational analytic with cross sectional study design with a population of 368 and a sample of 36 were divided into two groups, namely the above-average IQ and IQ group average. To determine the relationship SNP (rs867500) STX1A gene Exon 10 with a level of intelligence used X2 test (Chi-square). Results: The results showed not found SNPs in genes STX1A exon 10. Conclusion : STX1A Genes can be said to contribute to the collective intelligence of other genes, ie genes and gene IGFR2 FNBPL1 although there is no STX1A gene polymorphism in exon 10. Keywords: Gene STX1A Exon 10, polimorphism, SNP, intelectual, intelligence.